1986
DOI: 10.1080/15298668691389829
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Overexertion Injuries Using Biomechanical and Psychophysical Models

Abstract: This paper summarizes a three year epidemiological study conducted in five large industrial plants in order to evaluate the validity of two alternative modeling approaches to overexertion injury prediction. Detailed biomechanical and psychophysical job evaluations were performed for 55 industrial jobs comprised of 2934 potentially stressful manual materials handling tasks. The medical experiences of 6912 incumbent workers were monitored retrospectively for two years and prospectively for one year to establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(45 citation statements)
references
References 0 publications
1
43
1
Order By: Relevance
“…However, low-back-pain studies have shown that averaging does not predict risk well (e.g. Herrin, Jaraiedi, and Anderson 1986; Marras et al 1993; Norman et al 1998). It is worth noting that the ad hoc committee for the Revised NIOSH Lifting Equation did not believe that averaging of variables or Lifting Indexes was an appropriate method.…”
Section: Discussionmentioning
confidence: 99%
“…However, low-back-pain studies have shown that averaging does not predict risk well (e.g. Herrin, Jaraiedi, and Anderson 1986; Marras et al 1993; Norman et al 1998). It is worth noting that the ad hoc committee for the Revised NIOSH Lifting Equation did not believe that averaging of variables or Lifting Indexes was an appropriate method.…”
Section: Discussionmentioning
confidence: 99%
“…Support for these assumptions can be found in both NIOSH documents (NIOSH, 1981(NIOSH, , 1994 and in epidemiological studies by Herrin et al (1986), Bringham and Garg (1983), Anderson (1983), and Chaffin and Park (1973). However recent work by Leamon (1994) suggests that more research is needed in this area.…”
Section: The Criterion Selectedmentioning
confidence: 90%
“…Correction coefficients for limits of compressive forces the low-back by manual work. This force is considered a critical stress vector and good predictor of low-back damage (13). The values calculated by an equation published in the NIOSH Work Practices Guide for Manual Lifting (1981, revised in 1991) were accepted as limits for the compressive forces on the disc L4/L5, i.e.…”
Section: Discussionmentioning
confidence: 99%